2019
DOI: 10.1148/radiol.2019190199
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Phase II Trial of Radioembolization for Treatment of Uveal Melanoma Hepatic Metastasis

Abstract: veal melanoma (UM) is the most common primary malignant intraocular tumor in adults with an incidence of 5.1 cases per million in the United States (1-3). Up to 50% of patients with UM develop metastatic disease (3). The liver is the primary site of metastasis in greater than 90% of patients, and less than 10% of patients are candidates for surgical resection due to multiplicity of tumors at the time of diagnosis (3). Currently, there are no effective systemic therapies for patients with metastatic UM. In gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 28 publications
1
36
0
2
Order By: Relevance
“…When combined with other therapies, such as immunotherapy (ipilimumab, nivolumab, pembrolizumab, or Il-2) or immunoembolization (IE), OS rises slightly, even reaching 26 months in the study by Levey et al [ 125 ], in which extreme values were also obtained with 95 and 120 months of survival in two patients. Values that are considerably different from the median were also found in the study by Gonsalves [ 127 ].…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…When combined with other therapies, such as immunotherapy (ipilimumab, nivolumab, pembrolizumab, or Il-2) or immunoembolization (IE), OS rises slightly, even reaching 26 months in the study by Levey et al [ 125 ], in which extreme values were also obtained with 95 and 120 months of survival in two patients. Values that are considerably different from the median were also found in the study by Gonsalves [ 127 ].…”
Section: Resultssupporting
confidence: 54%
“…Treatment with SIRT offers a median OS at around 18 months, as first-line therapy, with very homogeneous results in the included studies [ 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 ]. When combined with other therapies, such as immunotherapy (ipilimumab, nivolumab, pembrolizumab, or Il-2) or immunoembolization (IE), OS rises slightly, even reaching 26 months in the study by Levey et al [ 125 ], in which extreme values were also obtained with 95 and 120 months of survival in two patients.…”
Section: Resultsmentioning
confidence: 99%
“…Yttrium-90 ( 90 Y) radioembolization is a form of selective internal radiation therapy, which has been effective for unresectable hepatocellular carcinoma (HCC) and multifocal hepatic metastases. [17][18][19] With hepatic metastases, some practice patterns reserve radioembolization for large or multifocal tumors. As a result, radioembolization is considered most often in the salvage setting when surgical resection is not feasible, and systemic therapy options have been exhausted.…”
mentioning
confidence: 99%
“…This study demonstrated similar median OS (18.5 months and 19.2 months) and 1-year survival rate (60.9 and 69.6%) between the two groups, respectively. Interestingly, the stabilization of hepatic disease was achieved in 87.0% of participants in groups A versus 58.3% in group B [ 201 ]. In a recent single arm, open labeled, nonrandomized study, the combination of yttrium-90 microspheres and intravenous cisplatin was well tolerated in mUM, but it failed at demonstrating sustained disease control with a median PFS of 3 months and median OS of 10 months [ 202 ].…”
Section: Treatment Of Metastatic Diseasementioning
confidence: 99%